THE IMPLEMENTATION OF GRAMMAR TRANSLATION METHOD TO BETTER SPEAKING COMPETENCE SUPPORTED BY DEVELOPING READING AND LISTENING SKILLS - Suseno, Edy; Purnomo, Heru; Nuryana, Amiatun (Sanata Dharma University Yogyakarta, 2022)
Learning to talk is difficult. The students had difficulty communicating their views to others. A study was done to assist them in correcting their flaw. The treatment enlisted the participation of 30 students from three different schools. Each school assigned ten individuals at random. There were a total of 13 learning opportunities. A pre-test was completed by the students in order to conduct such a treatment. It is a method of determining their prior understanding of the English language. The teacher uses the grammar translation method to begin the learning process. The teacher used podcasts to help students improve their grammatical understanding. The information was presented in the form of short stories and conversations. Students learn vocabulary, hearing, speaking, and grammar by modifying them. The students took a post-test at the end of the treatment. To answer the research question, data from the pre-test, post-test, and document were analyzed using the mixmethod method. From the analysis, it can be concluded that employing the grammar translation approach and podcast material can assist students improve their speaking skills. Other teachers could use the same outcome to teach related subjects. Other researchers can build on them to get other results.